Feminist fieldwork analysis - Kleinman, Sherryl (Qualitative research methods, 2007)
Guiding the researcher in not only how to think in terms of the feminist perspective, but how to translate their research into feminist practice and analysis, Sherryl Kleinman offers ten angles for feminist analysis, or ten things to keep in mind, when doing fieldwork and developing an analysis.